2020
DOI: 10.3389/fendo.2020.00172
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Physiological and Pathophysiological Functions of Stanniocalcin 2

Abstract: Stanniocalcin, a glycosylated peptide hormone, first discovered in a bony fish has originally been shown to play critical role in calcium and phosphate homeostasis. Two paralogs of stanniocalcin (STC1 and STC2) identified in mammals are widely expressed in variety of tissues. This review provides historical perspective on the discovery of fish and mammalian stanniocalcin, describes molecular regulation of STC2 gene, catalogs distribution as well as expression of STC2 in tissues, and provides key structural inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 79 publications
(134 reference statements)
1
36
0
Order By: Relevance
“…Previous studies have established the involvement of these six immune-related genes in invasion and metastasis of HNSCC tumor cells. More recently, both PLAU and STC2 were identified as oncogenes in HNSCC tumors, associated with immunosuppression and inflammation (Chang et al, 2003;Ieta et al, 2009;Na et al, 2015;Yang et al, 2017Yang et al, , 2020Joshi, 2020;Fang et al, 2021;Li et al, 2021). TNFRSF4 (also known as CD134/ OX40) is one of the representative targets of second-generation immune checkpoints, and its clinical efficacy has been observed by anti-TNFRSF4 (MEDI6469) therapy in HNSCC patients through regulating antigen-specific tumorinfiltrating T cells (Duhen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established the involvement of these six immune-related genes in invasion and metastasis of HNSCC tumor cells. More recently, both PLAU and STC2 were identified as oncogenes in HNSCC tumors, associated with immunosuppression and inflammation (Chang et al, 2003;Ieta et al, 2009;Na et al, 2015;Yang et al, 2017Yang et al, , 2020Joshi, 2020;Fang et al, 2021;Li et al, 2021). TNFRSF4 (also known as CD134/ OX40) is one of the representative targets of second-generation immune checkpoints, and its clinical efficacy has been observed by anti-TNFRSF4 (MEDI6469) therapy in HNSCC patients through regulating antigen-specific tumorinfiltrating T cells (Duhen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Huang et al showed that EXT2 is an independent prognostic factor for hepatocellular carcinoma [ 43 , 43 ]. Stanniocalcin (STC) is a glycosylated peptide hormone involved in calcium and phosphate homeostasis [ 44 ]. Among them, STC2 can regulate glucose homeostasis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of spatial conservation of the 11th cysteine residue in STC-2 compared to fish STC/STC-1, combined with the presence of four additional cysteine residues in this protein, leads to the prediction that STC-2 has a different tertiary structure when compared with other STCs. Despite some structural similarities between both STC-1 and STC-2, there is no evidence, thus far, to suggest that these proteins are capable of heterodimerisation ( Joshi, 2020 ). Another defining feature of STC-1, which is also conserved amongst the STCs, is the presence of an N-linked glycosylation consensus sequence (Asn-X-Thr/Ser).…”
Section: Introductionmentioning
confidence: 99%